ANALISIS PRODUKTIVITAS, BIAYA OPERASI DAN PAMADATAN TANAH PADA PENYARADAN TRAKTOR VALMET FORWARDER 890.3 DI AREAL HTI PROVINSI RIAU - Zakaria Basari; Dulsalam (BRIN Publishing, 2012)
The analisys of wood extraction using a Valmet forwarder tractor was carried out at industrial plantation forest PT. RAPP in Rian Province. The objective was to investigate productivity, operational cost, and soil compaction. The results showed that extraction productivity was 22,43 m³/hours. Average cost extraction average was Rp 20.935,-/m². Soil compaction was observed to be minor.